Numerical analysis of chemical-electrochemical mechanisms in rotating disk electrode systems - Leal, Pedro Henrique Moura (2019)
In this thesis, we present a thorough study of chemical-electrochemical mechanisms in rotating disk electrode systems. For that purpose, we used the finite differences method to discretize the exact convection-diffusion-reaction equations in linear or exponentially spaced grids, taking care to avoid additional simplifications. Different sets of parameters (rotation speed, Schmidt number and reaction rate constants) were used to analyse their effects on the limiting current density, on the diffusion impedance and on the electrohydrodynamic impedance. Our steady state results show that, even in systems with high reaction rate constants, the reaction layer hypothesis will fail for sufficiently high rotation speeds. Hence, a system with fast kinetics can be defined one for which the reaction layer hypothesis is valid for the whole rotation speed range investigated. The results for transient state show that combining diffusion impedance and electro-hydrodynamic impedance measurements is useful in identifying chemical-electrochemical mechanisms. Finally, we also investigated how varying the rotation speed, the equilibrium constant and the Schmidt numbers affects the impedance curves, which can be used for fitting experimental curves.